Case Report: Patient With Lung Adenocarcinoma With ALK-HLA-DRB1 Rearrangement Shows Impressive Progression-Free Survival After Sequential Crizotinib and Ceritinib Treatment - Gao, Peng; Tang, Kangning; Hao, Yuqiu; Li, Wei; Lv, Xuejiao; Li, Dapeng; Jia, Yuxi (Frontiers in Oncology, 2022)
The anaplastic lymphoma kinase (ALK) gene rearrangement is a driving mutation that underlies about 5-6% of non-small cell lung cancer (NSCLC) cases. Lung cancers that are ALK gene rearrangement-positive can be effectively treated with ALK inhibitors. However, the response of patients with rarer ALK gene rearrangements to ALK inhibitors remains unknown. Herein, we described a case of lung adenocarcinoma carrying ALK-HLA-DRB1 fusion in a 48-year-old nonsmoking woman. A similar case of ALK-HLA-DRB1 rearrangement in NSCLC has not been described previously neither in NSCLC nor in other disease. The patient achieved a progression- free survival of 18 months after sequential therapy consisting of crizotinib and then ceritinib during the follow-up. These findings provide basis for the application of ALK inhibitors in patients carrying the rare ALK-HLA-DRB1 fusion.